The influence of Hypothalamic-Pituitary-Adrenal (HPA) axis dysregulation on postpartum mental disorders - literature review and new perspectives - Kościuszko, Zuzanna; Sobiński, Adam; Czerwonka, Matylda; Kurza, Katarzyna; Agnieszka Kulczycka-Rowicka; Podolec, Julianna; Ciraolo, Silvia; Walczak, Anna; Lesiczka-Fedoryj, Katarzyna; Wojda, Joanna (Quality in Sport, 2025)
Introduction and Purpose of work: Postpartum depression is a psychiatric disorder associated with the changes in the endocrine system as well as in neuroimmune signaling. The purpose of this review is to investigate the meaning of neurosteroids that are link between postpartum depression and changes in Hypothalamic-Pituitary-Adrenal (HPA) axis, as well as to highlight the therapeutic implications. Review methods: This article is based on literature from PubMed, Google Scholar, and other databases. Observational studies, experimental studies, and meta-analyses on the HPA-axis and postpartum depression, including brain changes and neurosteroids as treatment options, were selected. Abbreviated description of the state of knowledge: Postpartum depression involves changes in the neuroendocrine and neuroimmune systems, often linked to HPA axis dysregulation affecting the CNS. Irregular GABAergic signaling is a key factor, influencing conditions like depression, anxiety, and PTSD. Neurosteroids have been used for treatment, and new options for postpartum depression are being explored. Hormonal shifts may also affect hippocampal and gray matter function. Summary: This review explores the connection between postpartum depression and hormonal changes in the HPA axis, highlighting its clinical importance. It calls for deeper insight into the condition’s pathophysiology, including hippocampal changes affecting memory and mood. Neurosteroid therapies show promise, but further research is needed on their role in HPA axis-related memory changes during postpartum. A comprehensive approach considering factors like sex, age, microbiome, stress, and diet is crucial.